2023
DOI: 10.3390/ijerph20031815
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Zonisamide and Ethanol on Various Types of Memory in Rats

Abstract: Background: Antiepileptic drugs might be useful in the treatment of alcohol use disorder. One of these drugs is zonisamide, which has been found to decrease alcohol intake and cravings. An important structure in the pathophysiology of addiction is the hippocampus. Memory deficits, which frequently occur in alcoholics, are associated with ethanol-induced changes in hippocampal plasticity and neurogenesis. The aim of this study was to assess the potential protective effect of zonisamide on memory in rats receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…In addition to enhancing the activity of GABA receptor systems, zonisamide may also reduce brain excitability by down-regulating GABA transporter proteins in the brain. A study conducted on rats found that treatment with zonisamide resulted in a significant reduction in ethanol consumption, as well as a differential influence on memory [ 99 ]. Additionally, another study conducted on mice found that zonisamide treatment led to a decrease in ethanol-induced conditioned place preference, suggesting a potential for the medication to reduce the rewarding effects of ethanol [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to enhancing the activity of GABA receptor systems, zonisamide may also reduce brain excitability by down-regulating GABA transporter proteins in the brain. A study conducted on rats found that treatment with zonisamide resulted in a significant reduction in ethanol consumption, as well as a differential influence on memory [ 99 ]. Additionally, another study conducted on mice found that zonisamide treatment led to a decrease in ethanol-induced conditioned place preference, suggesting a potential for the medication to reduce the rewarding effects of ethanol [ 92 ].…”
Section: Resultsmentioning
confidence: 99%